2019
DOI: 10.3390/ijms20030545
|View full text |Cite
|
Sign up to set email alerts
|

5p and 3p Strands of miR-34 Family Members Have Differential Effects in Cell Proliferation, Migration, and Invasion in Cervical Cancer Cells

Abstract: The micro RNA (miR)-34 family is composed of 5p and 3p strands of miR-34a, miR-34b, and miR-34c. The 5p strand’s expression and function is studied in cervical cancer. The 3p strand’s function and regulation remain to be elucidated. To study the function of the passenger strands of miR-34 family members, we overexpressed 5p and 3p strands using a synthetic miRNA in cervical cell lines. Cell proliferation was evaluated using crystal violet. Migration and invasion were tested using transwell assays, Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 84 publications
3
40
0
1
Order By: Relevance
“…The microRNA (miR)-34 family is composed of 5p and 3p strands of miR-34a, miR-34b and miR-34c. 10 MicroRNA-34b potently inhibited migration and invasion in metastatic prostate cancer cells by regulating the TGF-β pathway. 12 MicroRNA-34b acted as a tumour suppressor in the oestrogen-dependent growth of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microRNA (miR)-34 family is composed of 5p and 3p strands of miR-34a, miR-34b and miR-34c. 10 MicroRNA-34b potently inhibited migration and invasion in metastatic prostate cancer cells by regulating the TGF-β pathway. 12 MicroRNA-34b acted as a tumour suppressor in the oestrogen-dependent growth of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The microRNA (miR)‐34 family is composed of 5p and 3p strands of miR‐34a, miR‐34b and miR‐34c . Córdova‐Rivas S et al found that the 5p and 3p strands of miR‐34 family members had differential effects on cell proliferation, migration and invasion in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, hsa-mir-34c was strongly associated with the signature as its out-degree is the highest in the network as mentioned in the Figure 2. The miRNA hsa-mir-34c has differential effects in migration and cell proliferation in Cervical Cancer was already proved in the literature [22].…”
Section: Resultsmentioning
confidence: 89%
“…The two possible mature miRNAs of miR-125a, miR-125a-3p and miR-125a-5p, have inverse effects on invasion and migration of lung cancer cells (41). The 3p arm presents more individually regulated targets based on poorly sequence conservation (42). Therefore, the present study hypothesized that miR-34a-3p may exert a protective effect that may different from that of miR-34a-5p in RA.…”
Section: Discussionmentioning
confidence: 99%